2016
DOI: 10.1007/s12325-016-0456-9
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-Induced Bowel Dysfunction in Patients Undergoing Spine Surgery: Comparison of Oxycodone and Oxycodone-Naloxone Treatment

Abstract: IntroductionOpioids are needed for postoperative pain in spine surgery patients, but opioid-induced constipation is a harmful adverse event. The aim of this clinical trial was to compare the use of a controlled-release oxycodone-naloxone combination product with oxycodone controlled-release tablets in these patients. The main outcome measure was the prevalence of constipation at 7 days postoperatively assessed with a Bowel Function Index questionnaire. A follow-up assessment at 21 days after surgery was also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
3
5
0
Order By: Relevance
“…Moreover, it was found that oxycodone-naloxone tablets had a carry-over effect after seven days use of oxycodone two times a day; surveyed two weeks after opioid cessation, bowel function was superior after seven days of taking oxycodone-naloxone tablets compared to oxycodone tablets. 32 In the present study the opioid consumption and pain scores were similar or lower compared to our previous studies in similar settings. 4 , 29 , 30 Thus, it is unlikely that naloxone interfered with the analgesic efficacy of oxycodone.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, it was found that oxycodone-naloxone tablets had a carry-over effect after seven days use of oxycodone two times a day; surveyed two weeks after opioid cessation, bowel function was superior after seven days of taking oxycodone-naloxone tablets compared to oxycodone tablets. 32 In the present study the opioid consumption and pain scores were similar or lower compared to our previous studies in similar settings. 4 , 29 , 30 Thus, it is unlikely that naloxone interfered with the analgesic efficacy of oxycodone.…”
Section: Discussionsupporting
confidence: 81%
“…Guidelines recommend a tailored approach for the management of postoperative pain, and short‐acting oral opioids are generally preferred over long‐acting oral opioids for the immediate postoperative period, due in part to dose titration requirements . Our literature search identified 8 studies investigating short‐term administration of OXN PR to manage pain following surgery, including RCTs, open‐label studies, and retrospective studies (see Table ) . Together, the finding suggested broadly comparable analgesia with OXN PR vs. OXY PR, morphine, or other opioid analgesics, and some but not all studies also documented additional improvements in bowel function and early functional outcomes with OXN PR .…”
Section: Literature Searchmentioning
confidence: 98%
“…Our literature search identified 8 studies investigating short‐term administration of OXN PR to manage pain following surgery, including RCTs, open‐label studies, and retrospective studies (see Table ) . Together, the finding suggested broadly comparable analgesia with OXN PR vs. OXY PR, morphine, or other opioid analgesics, and some but not all studies also documented additional improvements in bowel function and early functional outcomes with OXN PR . High patient satisfaction (72% “very satisfied”) with OXN PR plus oral ketoprofen was reported in a study of patients following hip replacement .…”
Section: Literature Searchmentioning
confidence: 99%
“…Evidence indicates that in selected patients, a CR oxycodone/naloxone tablet can be useful in reducing OIBD; positive effects on OIBD are seen after 7 days of use. Moreover, combining naloxone with oxycodone seems to have a carry-on effect on OIBD [106,107].…”
Section: Cancer Pain and Cachexic Patientsmentioning
confidence: 99%